Hubungan Pengetahuan Dan Self Management Dengan Tingkat Stres Pasien Diabetes Melitus Yang Menjalani Diet - Wisudawati, Eka Rora Suci; Fauziah, Nila Alfa; Angriani, Dwi (JURNAL KESEHATAN TERAPAN, 2023)
Diabetes Mellitus (DM) is a chronic disease that occurs when the pancreas does not produce enough insulin or when the body cannot effectively use the insulin it produces. This usually causes hyperglycemia in DM patients. Hyperglycemia in DM that is not controlled properly can cause serious damage to body systems, especially nerves and blood vessels (World Health Organization, 2017). Factors that affect the level of DM diet stress are demographic levels, duration of illness and severity of illness, perception, self-motivation, self-confidence, participation in nutrition counseling, health workers, family support, regularity of health checks (Yulia, 2015). Other factors that can affect the stress level of DM diet are age, gender, education, knowledge, length of suffering and self-management (Kurniawan, 2020). The purpose of this study was to determine the relationship between knowledge and self management with stress levels of diabetes mellitus patients undergoing diet. The design of this study was a quantitative study with a cross sectional approach. The population in this study were all DM patients. The sampling technique in this study was random sampling, which was taken at random by 50 respondents. The results of the study There is a Relationship Between Knowledge and Self Management with Stress Levels of Diabetes Mellitus Patients Undergoing a Diet at the Kayuagung Ogan Komering Ilir Hospital in 2021.